Three-Dimensional Energy Transmitting Boundary in the Time Domain - Nakamura, Naohiro (Frontiers in Built Environment, 2015)
Although the energy transmitting boundary is accurate and efficient for the FEM earthquake response analysis, it could be applied in the frequency domain only. In the previous papers, the author proposed an earthquake response analysis method using the time domain energy transmitting boundary for two dimensional problems. In this paper, this technique is expanded for three dimensional problems. The inner field is supposed to be a hexahedron shape and the approximate time domain boundary is explained, first. Next, two dimensional anti-plane time domain boundary is studied for a part of the approximate three dimensional boundary method. Then, accuracy and efficiency of the proposed method are confirmed by example problems.